Critical appraisal of medical literature in undergraduate and postgraduate medical students - Mlika, Mona; Naceur, Abdelmajid; Dziri, Chadli; Loueslati, Mohamed Hédi; Mezni, Faouzi; Zakhama, Lilia; Labbene, Iheb; Jouini, Mohamed (Frontiers in Education, 2022)
Background:Critical appraisal of medical literature is a challenging competency which is mandatory in the practice of evidence-based medicine. The majority of the articles published in this field mainly assessed the students’ satisfaction or their cognitive knowledge. The authors aimed to assess the possibility of performing the same training of critical appraisal of medical literature to students with different backgrounds to highlight the link between the critical appraisal practice and the reflexive, cognitive, attitudes, and conative profile of the students according to their level. Methods:Students in the second year (SYME) and third year (TYME) of medical education and students performing continuing medical education (CME) and family doctors (FD) were invited to voluntarily participate in the training.The students were invited to answer a pre-requisite test and a self-assessment questionnaire before and after the training. At the end of the workshops, all of the students fulfilled a Fresno-adapted final test.Both self-assessment questionnaires were conceived by an expert committee assessing the cognitive, conative, motivational, and reflexive students’ profile. Also, the participants were invited to answer a semi-structured interview. Results:95 participants were included with 6 participants in SYME, 54 in TYME, 16 in CME, and 19 FD. The results highlighted the possibility of using the same program independently from the students' level.The analysis of the different pre- and postworkshop questionnaire scores highlighted mild or negative scores in the TYME and intermediate or good scores in the other levels.The variation of the mean scores according to the students' level revealed a significant difference in prerequisite, final test, preworkshop attitudes, postworkshop cognitive, postworkshop attitudes, postworkshop conative, and satisfaction scores. 11 students from different levels were interviewed. The content analysis highlighted 4 themes including the teaching organization, the institutional assessment, the impact on the research practice and the impact on the patients' management with the emphasis of the TYME students on the necessity of integrating the teaching and the assessment of the EBM principles in the curriculum Conclusion:Our results put emphasis on the necessity of introducing the teaching of critical appraisal of medical literature early in the curriculum in order to avoid negative behaviourism during the clerkship period.